Innovative Oral Treatments of Uterine Leiomyoma - Mohamed Sabry; Ayman Al-Hendy (Obstetrics and Gynecology International)
Uterine fibroids (leiomyoma), the benign tumors of the uterine wall, are very common cause of morbidity in reproductive age women usually in the form of excessive vaginal bleeding, chronic pelvic pain, miscarriage and infertility. These tumors are the leading indication for hysterectomy in the United States. Uterine fibroids are about 4 times higher in blacks compared to whites and constitute a major health disparity challenge. The estimated cost of uterine fibroids is up to $34.4 billion annually. Additionally, women who suffer from this disease and desire to maintain their future fertility have very limited treatment choices. Currently, there is no effective long-term medicinal treatment for uterine fibroids. While surgery has traditionally been the gold standard for the treatment of uterine fibroids, there is growing interest towards orally administered medications for the management of leiomyoma-related symptoms. In this paper, we will discuss these promising innovative oral medical treatments in detail.